Life cycle assessment of torrefied microalgal biomass using torrefaction severity index with the consideration of up-scaling production - Ubando, Aristotle T. (Animo Repository, 2020)
Microalgal biomass offers high biomass productivity, high photosynthetic efficiency, and low land requirement. However, there are challenges for the sustainable conversion of microalgae-to-biofuels. Through torrefaction, microalgal biomass can be upgraded to enhance its biomass characteristics. A life cycle assessment (LCA) is proposed to evaluate the environmental impact of the production of torrefied microalgal biomass (TMB). Using LCA, four different conversion pathways of generating TMB are considered and compared. The four scenarios include the effect of scaling-up the production to pilot-scale and comparing two cultivation systems (open pond and the photobioreactor). The analysis includes the influence of the torrefaction severity index (TSI) on environmental impacts. The results have shown that TSI is directly related to the global warming potential (GWP) wherein the influence of torrefaction temperature to the GWP was higher compared to the duration. The impact of the cultivation system was relatively higher compared to the other processes due to its high energy requirement. The scale-up effect of the cultivation phase resulted in a reduction of the GWP by 128% and 91% for the open pond and the photobioreactor, respectively. A net negative GWP impact is achieved in a pilot-scale with the use of an open pond cultivation system. With this configuration, the uptake of carbon dioxide during the cultivation outweighs the GWP impacts of producing TMB. Furthermore, the negative GWP result is lower compared with the results of previous studies on torrefaction and pyrolysis. © 2020 Elsevier Ltd